STRATEGI PENGHALANG SINAR MATAHARI OTOMATIS PADA UNIT HUNIAN RUMAH SUSUN DI PENJARINGANSARI SURABAYA - Syaifuddin Zuhri; Karina Firdauzy; Imam Ghozali (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2020)
Utilization of the abundant natural potential such as sunlight, especially in Surabaya, its a challenge in itself. This potential can be used for natural lighting in buildings. One of these efforts is how to make the potential of sunlight optimally utilized by controlling space openings that can adapt to the movement of the sun during a day. This research be using qualitative and quantitative methods to measure the adaptation of the movement of the sun barrier device which is placed in front of the unit's open space using a sun visor which is moved by a linear actuator controlled by an Arduino Microcontroller, while the LDR sensor is used to detect the direction of sunlight. From the research results, it was found that the imaging panel device was able to open and close according to the movement of sunlight with strong natural lighting between 10:00 to 15:00.